Tren Outsoursing Serta Dampaknya Terhadap Perusahaan Dan Karyawan (Studi Kasus Pada PT. XYZ Di Karawang) - Maesaroh, Imas; Nopiana, Medi (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2024)
This study aims to determine the trend of outsourcing and its implementation as well as the impact on the company and the outsourcing employees themselves. The research method used in this research is descriptive qualitative where the data collection technique used is through literature study, interviews, and direct observation of the object of research. The term outsourcing appeared in Indonesia since 1990 and its policy began after the economic crisis that hit the world, including Indonesia. the implementation of this outsourcing in terms of job security can reduce workers' rights, especially related to benefits, social security, and decent work guarantees. Outsourcing practice at PT. XYZ has done since the company was founded. Types of work outsourced include cleaning services, drivers, security, and other jobs that support company operations. The work that is outsourced is not core work, but work that is helpful or commonly called an assistant.